Skill Utilization of Older Workers in South Korea: The Effect of Diverse Types of Learning Experiences and Organizational Learning Supports - Hyunok Ryu; Doo Hun H Lim; Junghwan Kim; Intak Kwon (Adult Education Research Conference, 2018)
Using OECD’s 2013 PIAAC data, this study will examine how diverse types of learning experiences and organizational supports for learning influence older workers’ skill utilization in South Korea.
Keywords: older workers; formal learning; non-formal and informal learning; organizational learning supports; skill use